IMPLEMENTATION OF MODELING COMPONENTS CONTEXTUAL LEARNING ON STUDENTS AGRICULTURAL ENGLISH VOCABULARY MASTERY AT UMN AL WASHLIYAH - Vera Kristiana; Rezky Khoirina Tarihoran; Ayu Melati Ningsih (Fakultas Sastra UMN AL Washliyah, 2022)
English as an international language is used in various fields of life. One of them is in agriculture. One of the important components in learning English is vocabulary mastery. Mastery of vocabulary is considered an important part of the process of learning a language or developing one's ability in a language. Proper learning is needed so that students are able to master vocabulary easily and correctly, especially UMN Al Washliyah students in this case mastering agricultural English vocabulary. One of the effective learning approaches is the contextual approach (CTL). CTL is a learning concept that helps teachers relate subjects to real situations. In this CTL there are seven important elements, namely inquiry, questioning, constructivist, modeling, learning community, authentic assessment, and reflection. The seven elements can be applied in the whole learning process. This research focuses on one element, namely the modeling component. This study used a single group pre-test and post-test experimental design method. There are two types of data analysis methods used in this study. The first is descriptive statistics (to analyze data based on frequency distribution: mean, median, mode, standard deviation, histogram, and polygon) and the second is inferential analysis including homogeneity and normality tests.